2019
DOI: 10.3389/fnagi.2019.00080
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependent Neuroprotective Effect of Standardized Bee Venom Phospholipase A2 Against MPTP-Induced Parkinson’s Disease in Mice

Abstract: Parkinson’s disease (PD) is a chronic progressive neurodegenerative movement disorder characterized by the selective loss of dopaminergic neurons within the substantia nigra (SN). While the precise etiology of dopaminergic neuronal demise is elusive, multiple lines of evidence indicate that neuroinflammation is involved in the pathogenesis of PD. We have previously demonstrated that subcutaneous administration of bee venom (BV) phospholipase A 2 (bvPLA 2 ) suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 38 publications
(45 reference statements)
2
18
0
Order By: Relevance
“…As was mentioned before, bPLA2 has anti-inflammatory effects and induces protective effects against inflammatory conditions [117,148]. In a recent study, a mixture of 78% of bPLA2 and 15% of melittin was tested against PD in mice [49]. To initiate PD in mice, the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine model was used.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…As was mentioned before, bPLA2 has anti-inflammatory effects and induces protective effects against inflammatory conditions [117,148]. In a recent study, a mixture of 78% of bPLA2 and 15% of melittin was tested against PD in mice [49]. To initiate PD in mice, the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine model was used.…”
Section: Neuroprotective Effectsmentioning
confidence: 99%
“…Kim et al (2019) administered 20 mg/kg of MPTP, intraperitoneally in male C57BL/6J mice and evaluated the purified bee venom phospholipase-A2 against MPTP-induced neurotoxicity. Bee venom phospholipase-A2 treatment defeated the motor deficits (pole test) and inhibited loss of dopaminergic neurons within the substantia nigra in a dose-dependent manner in PD mice [ 134 ]. Liu et al (2020) administered MPTP at 15 mg/kg intraperitoneally to female mice and evaluated the effect of ACT001 (a fumarate salt of dimethylaminomicheliolide and a derivative of parthenolide) against Parkinsonian abnormality in female BALB/c mice.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…The therapeutic effect of bvPLA2 extends to the treatment for neurodegenerative diseases including AD [32]. Previous studies demonstrated the neuroprotective effect of bvPLA2 against Parkinson's Disease [33] and AD [9]. The main action of bvPLA2 on a cellular level is the suppression of immune responses through the stimulation of dendritic cells, which ultimately leads to an increased function of Treg cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…The area of the peak is used to measure the recovery of bvPLA2. The physical state of the final content of bvPLA2 was white powder and it was stored in freezing condition below −20 • C. It consisted of 93% of PLA2 and 7% of minor unknown constituents, as shown in previous report [33].…”
Section: Preparation Of Bvpla2mentioning
confidence: 97%
See 1 more Smart Citation